An Examination of Schizotypy, Creativity, and Wellbeing in Young Populations - Harrison E. Chapman; Sarah L. Asquith; Anna Abraham (Behavioral Sciences)
A wide array of scholarship has revealed the somewhat paradoxical relationship between creativity and mental health. On the one hand, substantial evidence demonstrates that certain forms of mental illness are associated with enhanced creativity. On the other hand, considerable evidence also confirms that engagement in creative pursuits improves wellbeing. In this paper, we examined the associations between creative potential, the pursuit of creative hobbies, wellbeing, and schizotypy in young people aged 16–22 years. Frequentist and Bayesian approaches revealed that a higher degree of disorganized schizotypal traits was associated with greater ideational fluency and more engagement in creative hobbies, and that a higher degree of interpersonal schizotypal traits was associated with lower wellbeing. The potential drivers of this dynamic association are discussed in this paper.